Rent-sharing in Portuguese banking - Monteiro, Natália (2007)
Using the fixed effects estimator and the dynamic panel data system-GMM estimator, on a sample of 75 banks, covering the period 1988-2005, this paper estimates how wages in the Portuguese banking sector depend on the employers ability to pay. The results indicate that wages are strongly positively correlated with profits even after controlling for firm and workforce characteristics. The Lester’s range of wages due to rent-sharing is 46% - 75% of the mean wage in the Portuguese banking sector.